Alluvial and lacustrine facies in an extensional basin - Turkmen, Ibrahim; Aksoy, Ercan; Tasgin, Calibe Koc (Pergamon-Elsevier Science Ltd, 2007)
During the Neogene, both strike-slip and extensional regimes coexisted, giving rise to a number of fault-bounded basins in eastern Turkey. One of these basins, the Malatya basin, contains a thick sequence (up to 2000 m) of alluvial and lacustrine deposits. This paper focuses on the Miocene alluvial and lacustrine deposits in the northern part of the basin. Alluvial and lacustrine deposits in the study area, having a thickness over 1200 m, are divided into three units on the basis of their vertical sequential changes and lithologic characteristics. These are the lower alluvial unit, lacustrine unit, and upper alluvial unit. The lower alluvial unit is composed of stratified conglomerate (Gm), planar cross-stratified conglomerate (Gp), trough cross-stratified sandstone (St), planar cross-stratified sandstone (Sp), horizontally stratified sandstone (Sh), ripple cross-laminated sandstone (Sr), red mudstone (Fm), carbonaceous claystone (Fl1), and rarely limestone (Pf). Facies Gm, Gp, and Sh characterize alluvial fan to sheetflood deposits. Facies St, Sp, Sh, and Sr are interpreted as braided stream to sheetflood deposits. Facies Fm, Fl1 and siltstone are interpreted as deposits in an alluvial plain system with an ephemeral setting. Carbonaceous claystone (Fl1) and limestone (Pf) are interpreted as a shallow lake, situated as a distal environment in alluvial plain. The middle unit, interpreted as channel/crevasse-splay, swamp and lacustrine deposits, is composed of interbedded sand stone-siltstone-grey claystone (SF), low-angle cross-stratified sandstone (Sl), planar cross-stratified sandstone (Sp), limestone (N), carbonaceous claystone (Fl1), marl (Fl2), and coal (C). The upper alluvial unit is composed of Gm, Gp, St, Sp, Sh, Sr, and Fm characterizing a low sinuosity river. Most of the alluvial input into the basin was from the north, northeast, and east. Soft-sediment deformation structures (slump folds) which indicate seismically active areas were formed within the lacustrine facies. The sediment supply, lake level fluctuation, and facies architecture were mainly controlled by synsedimentary tectonism. (c) 2006 Elsevier Ltd. Ail rights reserved.
Keywords: extensional basin; alluvial fan; fluvial; lacustrine; Turkey; Malatya basin; Neogene